Seed Priming to Enhance Plant Stand under Stressed Environment: A Review - HEMENDER; VS MOR; PRADEEP KUMAR DALAL; SUSHMA SHARMA; AXAY BHUKER; PUNEETH RAJ MS (Seed Research, 2026)
Seed germination is the very first stage of a plant’s life. For a successful crop yield, good germination is essential which is the most vulnerable stage to any unfavourable environmental condition. Crop plants are subjected to a variety of stresses throughout their life cycle because of increasing stress frequency in view of global climate change. Seed germination, being the very first stage, defines the plant growth and development in a particular environment. Thus, any approach that aids the crop in successful plant establishment is worth putting to use in unfavourable field conditions. Seed priming is a low-cost approach that promotes homogeneous seed germination and early seedling growth in a variety of conditions. The most basic form of seed priming is hydropriming which includes soaking seeds in water for a specific period of time. The use of salt, plant growth regulators, mineral nutrients, biological agents, and other chemicals as the priming agents have been developed over time for increased seed/seedling performance. Hence, this review has been compiled for effect of different seed priming techniques on germination characteristics as well as overall crop performance under both stressed and non-stressed conditions.